APPLICATIONS OF OVERLOAD COOPERATION DISTRO WEB USING PHP AND MYSQL - Rito HENDRAWAN; Ristyawati Ristyawati., SKom, MMSI (Jurnal Sistem Informasi, 2006)
To obtain information fast and very broad in scope is not so difficult. The development of the Internet to solve various problems of these things. With this site is expected to be the appropriate information media to find information that does not hit the time, everywhere and instantly. In addition, admin can even make it easier to take care of the development site from day to day.   Language described in this paper is the development of a Web-based application as a medium of information, which is intended for users who access the site. This site created using PHP which uses the concept of server side programming in which this paper does not depend explorer (browser) that runs karna this paper is the server and the results will be displayed in the client's occupiers.